Iceland : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2006)
Given its small size and openness, the Icelandic economy has been subject to large shocks. Systematic coordination of monetary and fiscal policy, however, could help improve the inflation-output variability trade-off. The fiscal rule is designed to simultaneously ensure a consistently countercyclical fiscal stance and achieve a stable public debt target. The parameter values of the model are estimated from the quarterly data using a Bayesian technique. To assess how the introduction of the fiscal policy changes the inflation-output variability trade-off in Iceland, the paper compares the efficiency policy frontiers.